Translation and Validation of the FOUR Scale for Children and its Use as Outcome Predictor: A Pilot Study - Ferreira, Sofia Simões (2017)
Introduction: The Full Outline of UnResponsiveness - FOUR scale has been previously validated to assess impaired consciousness in the adult population. The aim of this study is the translation into Portuguese and validation of the FOUR scale in the pediatric population. The study also compares the FOUR scale and Glasgow coma scale score ratings and the clinical outcome of patients hospitalized in Pediatric Intensive Care Units.Material and Methods: This study prospectively rated patients admitted to the Pediatric Intensive Care Units with impaired consciousness during one year. Both scales were applied daily to patients by three types of examiners: intensivists, residents and nurses, from the moment of admission until clinical discharge. Neurological sequelae was evaluated using the King’s Outcome Scale for Childhood Head Injury - KOSCHI.Results: Twenty seven patients between one and 17 years of age were included. Both scales are reliable and inter-rater reliability was greater for the FOUR score. Glasgow coma scale showed a minimum score in eight evaluations, whereas the FOUR scale obtained the minimum score in only two of these evaluations. In both scales there was a strong association between the admission score and the patient’s outcome (area under curve FOUR = 0.939, versus Glasgow coma scale = 0.925).Discussion: The FOUR scale provides more neurological information than Glasgow coma scale in patients with impaired consciousness and has prognostic interest.Conclusion: The FOUR scale can be applied in patients admitted with impaired consciousness in Pediatric Intensive Care Units. We think that a multicenter study would be very beneficial for confirming and generalizing these results.